Acceptability to patients of screening disposable transnasal endoscopy: qualitative interview analysis - Laurence B Lovat; Sarmed S Sami; Krish Ragunath; John Mcgoran; John De Caestecker; Andrea Bennett; Joanne Cooper; Neil Guha (BMJ Open)
Objectives Screening in selected high risk populations for Barrett’s oesophagus (BO) and oesophageal varices (OVs) has been proposed, but there are obstacles with conventional oesophagogastroduodenoscopy (C-OGD), including patient acceptability. Portable and disposable office-based transnasal endoscopy (TNE) is a feasible and accurate alternative to C-OGD that may have use in primary and secondary care. This article outlines a qualitative analysis of patient experiences of TNE and C-OGD in order to gain an insight into an acceptable delivery of an endoscopic screening service.Design Purposeful sampling identified 23 participants who then underwent semi-structured interviews to determine their experiences of both procedures. Thematic analysis was conducted to derive meaning from their lived experiences.Setting A secondary care endoscopy unit, clinic room and interview room.Participants Patients referred for BO or OV surveillance and for endoscopy to investigate dyspepsia underwent unsedated TNE using the EG Scan II device followed by C-OGD with or without sedation (patient choice), as part of a clinical trial.Results The themes that arose from our analysis were: inclusivity in one’s own healthcare, comfort level and convenience, validity of the procedure and application to a screening population and a sense of altruism and reciprocity. Positive aspects of TNE included participant empowerment, reduced discomfort and avoidance of conscious sedation. Participants felt that if TNE screening was of proven efficacy it would be welcomed, though views on use in a community setting were mixed.Conclusions Most patients preferred TNE to unsedated C-OGD and the reasons they gave featured strongly in the emerging themes. Preferences between TNE and sedated C-OGD were more subtle, with equivalent comfort scores but merits and drawbacks of both being discussed. This information identifies opportunities and challenges in establishing an endoscopic screening service.Trialregistration numberISRCTNregistry identifier: 70595405; Pre-results.